EFEKTIVITAS MODEL PEMBELAJARAN 3CM DENGAN PENDEKATAN DEEP LEARNING PADA HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS V DI UPTD SD INPRES MOEPALI - Manapa, Imanuel Yosafat Hadi; Buling, Reny Tiansi (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to compare student learning outcomes before and after using the 3CM learning model with a deep learning approach. This quantitative research employed an experimental method with a pre-experimental one-group pretest-posttest design. The subjects were all fifth-grade students of SD Inpres Moepali, totaling 33 students, selected using saturated sampling. Data were collected through pretest and posttest assessments. The data analysis employed a t-test. The results showed that the average pretest score was 48.12, while the average posttest score increased to 80.60. The t-test results at ? = 0.05 yielded t-table = 1.694 and t-count = 23.336. These findings indicate that student learning outcomes significantly improved after implementing the 3CM learning model with a deep learning approach.